Experimental Investigation on the Field-Dependent Properties of Magnetorheological Elastomer with Circular Honeycomb Holes - Yu, Miao; Xing, Zhiwei; Zheng, Xing; Fu, Jie; Choi, Seung-Bok (Frontiers in Materials, 2015)
In order to enhance adjustable mechanical properties of a specific magnetorheological elastomer (MRE), this study presents a new exterior structure of MRE by punching circular honeycomb holes on the MRE samples. Seven silicone rubber MRE samples with the same component are fabricated and then punched holes with different numbers and diameters. The influence of different porosities on the mechanical properties of MRE under various magnetic fields is experimentally investigated by using a rheometer with electromagnetic suite. It is shown from experimental investigation that the porosity of MRE samples has a significant impact on the performance of MRE; the shear storage modulus (MR effect) and the loss factor is greatly increased. It is also observed that all the field-induced mechanical properties of the samples attain their respective maximum performance when the porosity increases to a critical value. The experimental results presented in this work directly indicate that high performances of the field-dependent mechanical and rheological properties can be achieved by means of external alternative structures such as honeycomb holes.